2009
DOI: 10.1193/1.3089367
|View full text |Cite
|
Sign up to set email alerts
|

Performance of School Buildings in Turkey During the 1999 Düzce and the 2003 Bingöl Earthquakes

Abstract: Several school buildings were surveyed in the disaster areas of the Marmara (17 August 1999, [Formula: see text]), Düzce (12 November 1999, [Formula: see text]), and Bingöl (1 May 2003, [Formula: see text]) earthquakes in Turkey. Among them, 21 reinforced concrete buildings were found to have an identical floor plan. Lateral load resisting structural system consisted of reinforced concrete frames (moment-resisting frame) in 16 of the buildings and structural concrete walls integrated with the moment-resisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
0
13
0
Order By: Relevance
“…Kwon confirmed in analysis results that shear force demand on columns with infill walls was significantly higher than those without infill walls. Turel Gur et al (2007) made three surveys of damage to concrete structures following the 1999 Marmara and Düzce earthquakes. They observed that the sole severely damaged structure was damaged not by failure in the ground story, as all the other school buildings, but by failure of captive columns at basement level as a result of discontinuity of the foundation walls in height.…”
Section: Short Columnmentioning
confidence: 99%
“…Kwon confirmed in analysis results that shear force demand on columns with infill walls was significantly higher than those without infill walls. Turel Gur et al (2007) made three surveys of damage to concrete structures following the 1999 Marmara and Düzce earthquakes. They observed that the sole severely damaged structure was damaged not by failure in the ground story, as all the other school buildings, but by failure of captive columns at basement level as a result of discontinuity of the foundation walls in height.…”
Section: Short Columnmentioning
confidence: 99%
“…We believe that is a major source of difference due to the fact that lateral load resisting systems consisting of moment-frames with unreinforced hollow clay-tile infill walls have very limited displacement capacity. In fact, the extremely poor performance of school buildings with moment-frame systems with unreinforced hollow clay-tile infill walls during the 1999 Duzce and the less intense 2003 Bingol, Turkey earthquakes have been documented extensively (Gur et al 2009). …”
Section: Review Of the Results From The Analysesmentioning
confidence: 98%
“…Since the 1992 Erzincan earthquake in Turkey, performances of several hundred buildings affected by strong earthquakes have been reviewed using the priority index (Ozcebe et al 2004;Donmez and Pujol 2005;Gur et al 2009). The priority index for a building is computed as the ratio of ''effective'' column and wall crosssectional areas to the total floor area of the building:…”
Section: Hassan Index-based Vulnerability Rankingmentioning
confidence: 99%
“…The performance of reinforced concrete (RC) beam‐column joints has long been recognized as a significant factor that affects the overall behavior of RC moment frames subjected to seismic loading . Several recent large earthquakes have caused considerable fatalities and financial losses because of the collapse of RC structures, and post‐earthquake surveys have led to the observation that damage to RC moment frames was frequently concentrated in the beam‐column joints, primarily attributed to the absence of transverse reinforcement and to insufficient bond length of the beam bottom bars in the joint panel zone . These observations have resulted in research considering the repair and improvement of damaged beam‐column joints, and it has been established that if an earthquake‐damaged building can be returned to the correct vertical alignment (less than 1% drift ratio for RC frames ), then the damaged building can potentially be rehabilitated so that its performance is comparable with that of a new building compliant with current design standards.…”
Section: Introductionmentioning
confidence: 99%